Exploring the roots of sustainable development. Advances and challenges - Villegas González, Crisálida Victoria; Alfonzo Villegas, Nohelia Yaneth (Conexiones UG, 2024)
The topic of sustainable development is considered controversial and complex, as evidence of which there are numerous institutional documents resulting from summits and conferences, which are still valid, as a product of research and reflections by authors from different countries and organizations. Hence, the objective of the article is to expose the roots of sustainable development, its advances and challenges, based on a documentary review, mainly in the period between 2018-2023. It was concluded that: (a) some authors consider that the concept has been manipulated as a political strategy to provide continuity to the existing development model or justify policies and practices; as well as that its achievements at the Latin American level are insufficient; (b) there are also advances such as the conception of sustainable development as a multidimensional process; (c) its achievement requires more and better training of citizens, research from more comprehensive approaches such as transcomplex thinking and more comprehensive policies, the product of more participatory management, where the State continues to play a fundamental role.
Keywords: Environment; Sustainable Development; Economy; Social